Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if a^4+b^4=a^2b^2 show that a^6+b^6=0 showshowshowshowshowshowshowshowshowshowshowshowshowshowshow

if a^4+b^4=a^2b^2
 
 
show that a^6+b^6=0
showshowshowshowshowshowshowshowshowshowshowshowshowshowshow

Grade:9

1 Answers

Arun
25763 Points
2 years ago
Given, a^(4) + b^(4) = a^(2)b^(2)
To Prove = a^(6) + b^(6) = 0
We can write a^(6)+b^(6) as (a^(2))^(3) + (b^(2))^(3)
So, we got the formula of x^(3)+y^(3)
where x= a^2 and y= b^(2)
Now open the formula = 
x^3+y^3 = (x+y)(x^2+y^2-xy)
Now, put the values of x and y,
a^6+b^6 = (a^2+b^2)(a^4+b^4-a^2b^2)
and given, a^4+b^4=a^2b^2
So, 
a^6+b^6 = (a^2+b^2)(a^2b^2 - a^2b^2)
therefore, 
a^6+b^6 = 0
 
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free